Risk factors of brain metastasis during the course of EGFR-TKIs therapy for patients with EGFR-mutated advanced lung adenocarcinoma - Ma, Xiaoyan (Oncotarget, 2016)
Controversial value of prophylactic cranial irradiation (PCI) in NSCLC in terms of survival benefit prompted us to explore the possible risk factors for brain metastasis (BM) during the course of EGFR-TKIs therapy from EGFR-mutated advanced lung adenocarcinoma and identify the potential population most likely to benefit from PCI, because BM remains a therapeutically challenging issue. We retrospectively reviewed the records of 134 patients with EGFR-mutated advanced lung adenocarcinoma between 2008 and 2012. The cumulative incidence of BM was calculated by the Kaplan-Meier method, and Multivariate Cox regression analysis was used to assess the independent risk factors for BM. Thirty-four patients (34/134, 25.4%) developed BM during the course of EGFR-TKIs therapy. Moreover, the Multivariate analysis indicated that age ≤ 53 years (HR: 2.751, 95 % CI: 1.326-5.707; p = 0.007), serum carcinoembryonic antigen (CEA) ≥ 23 ng/mL (HR: 3.197, 95 % CI: 1.512-6.758; p = 0.002) and EGFR exon 21 point mutations (HR: 2.769, 95 % CI: 1.355-5.659; p= 0.005) were the independent high-risk factors for developing BM, which could offer important insights into the individualized treatment. Further studies are warranted to validate our findings.